PENGARUH PRODUK DOMESTIK REGIONAL BRUTO(PDRB), JUMLAH PENDUDUK, INVESTASI SWASTATERHADAP REALISASI PENDAPATAN ASLI DAERAH(PAD) (Studi Empiris pada Kabupaten/Kota Di Propinsi Jawa Tengah Tahun 2011-2014) - FIRYAL NUR IKBAR, ATIKAH, Dr. Erma Setiawati, MM, CA (2017)
The purposes of this research are to find out and analyze the impact of gross regional domestic product (PDRB), population, private investment towards the realization of local original revenue (PAD) in the district/city in central java province in 2011-2014. This research uses quantitative method with secondary data obtained of statistical center body (BPS) and DJKP (Directorate general of fiscal balance) central java province. Population in this research is all sub-province/city of in central java province in 2011-2014 Amount of sample in this study were 35 district / city for 4 year. Method of sample collection using purposive sampling techniques. The analytical tool used include normality test, multicollinearity, heterocodesticity test, test autokolerasi multipe linear regression analysis, F test, test the confficient of determinaton R2 and t test. Based on the results of data analisis can be conclude that the variable gross regional domestic product (PDRB) a negative impact on the revenue, while the population of and effect on revenue. Then in private investment variables affect the revenue.